ADOPTION AND UTILIZATION OF THE FAMTECHCARE TELEHEALTH INTERVENTION FOR IN-HOME DEMENTIA CAREGIVER SUPPORT. (11th November 2018) - Shaw, C; Williams, K; Perkhounkova, E; Blyler, D; Seabold, D; Hein, M
Abstract: Supporting in-home dementia caregivers is a national priority. Caregivers report interest in using technology to assist with care, but have few resources. FamTechCare is a telehealth intervention that provides individualized guidance based on video recordings that caregivers create of care situations. This analysis reports the adoption and utilization of FamTechCare by in-home dementia caregivers. Descriptive statistics related to engagement in FamTechCare were collected. Bivariate relationships between participant characteristics (caregiver age, dyad relationship, dementia behavioral symptoms, and dementia stage) and rates of participation (number of videos and weeks receiving feedback) were analyzed using Spearman correlations and Kruskal-Wallis test. To date, a total of 86 dyads have been enrolled and randomized to the FamTechCare intervention or attention control. 16.3% (n=14) of the dyads have withdrawn from the trial related to study burden (n=3), long-term care or hospital admission (n=8), discomfort being video recorded (n=2), or reason not given (n=1). Seven dyads were excluded from bivariate analysis due to early withdrawal. Rates of participation were not related to participant characteristics, but intervention caregivers submitted more videos than controls (p=.02). Over the 12-week trial, intervention dyads (n=37) submitted on average 16.4 (±12.2) videos and received expert feedback based on the videos during 8.8 (±2.6) weeks. Rates of participation were not related to participant characteristics. In-home dementia caregivers successfully adopt the FamTechCare intervention regardless of caregiver age, dyad relationship, disease severity, and behavioral symptoms. Feedback based on videos was an important predictor for engagement. The FamTechCare intervention can be successfully adopted by dementia caregivers.